The Effect of the Pre-Islamic (al-Jahiliyya) Moral Values in the Poetry of Abu Firas alHamdani - Gh Al-Izaybawee, Ahmed; Arab, Abbas; Nazeri, Hossain (International Journal of Psychosocial Rehabilitation, 2020)
High moral values were manifested in the poetry of the pre-Islamic era through the commitment of most poets to the values and ideals that reflected the reality of the Arab human being in that era. The Arab sons inherited these virtuous values in their society and practiced them in their social life until these values became customs and traditions. The noble values of the poet and great knight Abu Firas al-Hamdani, were abstinence, generosity, loyalty, patience, and self-pride, which were significantly present in his poetry. This study sought to show the impact of those values that were prevalent in the pre-Islamic era in the poetry of one of the great Abbasid poets. Those values reflect the moral and heroic reality of the Arab knight Abu Firas under the turmoil of conflicts experienced during the rule of the Hamdanids in Aleppo. Despite all the challenges faced by the poet, he adhered to those original Arab moral values, which were his basic guide to express himself and the sublime values of his people.